The differential associations of depression and diabetes distress with quality of life domains in type 2 diabetes - Carper, Matthew M. (2013)
The present investigation aimed to understand quality of life domains relevant to adults with type 2 diabetes mellitus (T2DM), and the relative associations of depression and diabetes distress with these domains. Participants were 146 individuals with T2DM who were recruited for entry into a randomized controlled trial of cognitive behavioral therapy for adherence and depression. We conducted an exploratory factor analysis on the Quality of Life Inventory (QOLI) to establish domains of quality of life relevant to this patient population. Hierarchical multiple regression models were evaluated for each domain that emerged to determine independent associations of depression severity and diabetes distress with quality of life independent of demographic and illness factors. Results suggested four quality of life domains: achievement, psychosocial growth, interpersonal relationships, and environment, accounting for 60.1 % of variance in total QOLI scores. Depression severity was associated with poorer quality of life on the achievement, psychosocial growth, and environment domains (p’s < 0.01), while diabetes distress was associated with poorer quality of life on the achievement (p < 0.001) domain and marginally associated with quality of life on the psychosocial growth (p < 0.10) domain. Interventions designed to address both depression and diabetes distress may lead to better quality of life outcomes than a generalized depression intervention or an intervention for diabetes alone.